2018
DOI: 10.1101/458083
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A completeCannabischromosome assembly and adaptive admixture for elevated cannabidiol (CBD) content

Abstract: Cannabis has been cultivated for millennia with distinct cultivars providing either fiber and grain or tetrahydrocannabinol. Recent demand for cannabidiol rather than 20 tetrahydrocannabinol has favored the breeding of admixed cultivars with extremely high cannabidiol content. Despite several draft Cannabis genomes, the genomic structure of cannabinoid synthase loci has remained elusive. A genetic map derived from a tetrahydrocannabinol/cannabidiol segregating population and a complete chromosome assembly from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
144
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(150 citation statements)
references
References 56 publications
(85 reference statements)
4
144
2
Order By: Relevance
“…Since the CCP-1 assay examines CBDAS only and CBDAS and THCAS are not allelic, it is possible that a plant with a recombination between CBDAS and THCAS would not be scored correctly. However, we did not detect this in any of our samples, and the tight linkage in repulsion between CBDAS and THCAS is well established Grassa et al, 2018;Weiblen et al, 2015). The mean Δ 9 -THC and total potential THC concentrations as percent dry matter were significantly different in each chemotype.…”
Section: Ccp-1 Cannabinoid Chemotype Assaycontrasting
confidence: 56%
See 1 more Smart Citation
“…Since the CCP-1 assay examines CBDAS only and CBDAS and THCAS are not allelic, it is possible that a plant with a recombination between CBDAS and THCAS would not be scored correctly. However, we did not detect this in any of our samples, and the tight linkage in repulsion between CBDAS and THCAS is well established Grassa et al, 2018;Weiblen et al, 2015). The mean Δ 9 -THC and total potential THC concentrations as percent dry matter were significantly different in each chemotype.…”
Section: Ccp-1 Cannabinoid Chemotype Assaycontrasting
confidence: 56%
“…The genetic structure of CBDAS and THCAS have been recently elucidated (Grassa et al, 2018;Laverty et al, 2019). While the genes are highly alike, sharing 84% amino acid identity (Onofri, de Meijer, & Mandolino, 2015), they are not allelic or at equivalent loci.…”
mentioning
confidence: 99%
“…The genome architecture among different plants varies considerably. Arabidopsis and rice, for example, have relatively small subtelomeric regions (The Arabidopsis Genome Initative, ; Mizuno et al ., ), whereas other plants show increased recombination rates towards the chromosome ends and relatively large distal telomeric regions with increased gene content, very similar to what is seen in wheat (Choulet et al ., ; Glover et al ., ; Li et al ., ; Lambing et al ., ; Grassa et al ., ; Sun et al ., ; Laverty et al ., ). It will be interesting to see whether similar dynamics of MIKC‐type MADS‐box gene duplications can be observed in those species.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these challenges we have built considerably on the existing knowledge of the Cannabis proteome and have generated a relatively complete picture of the protein composition of the plants we have analyzed to date. Genomic analysis has identified approximately 25,000 protein coding regions, a number comparable to that of humans in a Cannabis chromosome assembly 33 . While exact numbers are still currently debated, no study to our knowledge as identified more 20,000 or more unique protein groups in humans.…”
Section: Results and Conclusion Peptide And Protein Identificationsmentioning
confidence: 99%
“…All samples were obtained by Think20Labs under the guidelines of the MMCC regulations in accordance with a temporary license granted under COMAR 10.62. 33. 13 A recent study described the optimization of digestion conditions for the proteomic analysis of Cannabis flowers and performed similar experiments as the ones described here.…”
Section: Materials and Methods Samplesmentioning
confidence: 97%